Assessment of the Potential of Umbrella Thorn [Vachellia tortilis (Forssk.) Galasso & Banfi] for the Rehabilitation of Sub-Sahelian Mining Sites at Essakane, North-Eastern Burkina Faso - Yonli, Hendi Hermann; Campagnac, Estelle; Haro, Hadou; Ouedraogo, Maurice; Vézina, Marie-Michelle; Khasa, Damase P.; Dianda, Mahamadi (Frontiers in Ecology and Evolution, 2022)
Establishment of plant communities at mine sites with significant disturbances depends on factors such as the presence of efficient mycorrhizal fungi and rhizobia. Field and greenhouse experiments were conducted to assess growth performance of umbrella thorn as a potential tree species for reforestation of mine sites in arid areas. In a first experiment, seedlings were transplanted onto waste rock (WR) and tailings (TLG) with a high arsenic content on the sites of the Essakane gold mine. Trees were assessed for growth and survival three years after planting. Second, soil samples were taken from four sites across a disturbance gradient from mining waste (WR and TLG), artisanal gold mining (AMS) to undisturbed natural soil (NS). Each soil was planted in pots with two separate leguminous trap crops (cowpea and umbrella thorn) to check for the presence of microsymbionts. At three years, trees grew better on TLG soils with more arsenic contamination than RWs in the field. Although tree establishment was moderate with less than 50% survival, the overall results suggest the ability of the umbrella thorn to tolerate heavy-metal tresses, and therefore its potential for reforestation. Soil pH has shown strong effects on soil nutrient content. In particular, ammonium was the dominant form of mineral nitrogen (N) in the more neutral NS soils, while nitrate was present in the more alkaline WRs. Denitrification is believed to result in high N loss where nitrate dominates, reflecting the poor performance of N-deficient trees on WRs compared to TLG soils. Growth trends of umbrella thorn in potted-soils were consistent with those reported on TLG and WR soils in plantations. In addition, cowpea and umbrella thorn showed lower symbiotic root colonization on mine wastes compared to natural soils, suggesting possibility of improving umbrella thorn performance through identification of efficient microsymbionts that are suitable for mine site environments.